Needful things - King, Stephen, 1947- (Viking, 1991)
A wonderful new store has opened in the little town of Castle Rock, Maine. Whatever your heart<U+2019>s secret desire<U+2014>sexual pleasure, wealth, power, or even more precious things<U+2014>it<U+2019>s for sale. And even though every item has a nerve-shattering price, the owner is always ready to make a bargain. In this chilling novel by one of the most potent imaginations of our time, evil is on a shopping spree and out to scare you witless.